2022
DOI: 10.1039/d1ce01606g
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and microstructural analysis of triangular defects in 4H-SiC homoepitaxial layers

Abstract: The surface morphologies and microstructures of triangular defects in 4H-SiC homoepitaxial layers were investigated by a laser confocal microscopy before and after molten KOH etching and microwave plasma etching. Three...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…These triangular defects showed different surface morphologies [9][10][11][12][13][14]. Studies on the 4H/3C boundary have shown that the 4H and 3C structures exhibit a coherent crystallographic orientation relationship, and the (0001) planes in the 4H-SiC are coherently connected to the (111) planes of the 3C-SiC [9]. Additionally, 3C-SiC nanowires with different states of stacking faults were observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These triangular defects showed different surface morphologies [9][10][11][12][13][14]. Studies on the 4H/3C boundary have shown that the 4H and 3C structures exhibit a coherent crystallographic orientation relationship, and the (0001) planes in the 4H-SiC are coherently connected to the (111) planes of the 3C-SiC [9]. Additionally, 3C-SiC nanowires with different states of stacking faults were observed.…”
Section: Introductionmentioning
confidence: 99%
“…According to the report, the triangular defects, which were intrinsically 3C-SiC polytype inclusions, were observed in the fabrication of 4H-SiC epitaxial layers grown via the CVD method [7,8]. These triangular defects showed different surface morphologies [9][10][11][12][13][14]. Studies on the 4H/3C boundary have shown that the 4H and 3C structures exhibit a coherent crystallographic orientation relationship, and the (0001) planes in the 4H-SiC are coherently connected to the (111) planes of the 3C-SiC [9].…”
Section: Introductionmentioning
confidence: 99%